Capital Gains, Dividend Yields, and Expected Inflation - Pilotte, Eugene A. (Journal of Finance, 2003)
One explanation for the negative relationship between short‐horizon stock returns and inflation is that inflation proxies (inversely) for expected future real output. In this paper, I examine the possibility that inflation also proxies for variation in real price/dividend ratios (excess returns). I show that when the covariance between real price/dividend ratios and inflation is nonzero, the relationship between returns and expected inflation differs for the two components of returns: dividend yields and capital gains returns. My empirical evidence demonstrates that dividend yields and capital gains are related differently to expected inflation in U.S. and foreign markets.